Evaluating the Effectiveness of a Local Primary Care Incentive Scheme: A Difference-in-Differences Study. (June 2022) - Khedmati Morasae, Esmaeil; Rose, Tanith C.; Gabbay, Mark; Buckels, Laura; Morris, Colette; Poll, Sharon; Goodall, Mark; Barnett, Rob; Barr, Ben
National financial incentive schemes for improving the quality of primary care have come under criticism in the United Kingdom, leading to calls for localized alternatives. This study investigated whether a local general practice incentive-based quality improvement scheme launched in 2011 in a city in the North West of England was associated with a reduction in all-cause emergency hospital admissions. Difference-in-differences analysis was used to compare the change in emergency admission rates in the intervention city, to the change in a matched comparison population. Emergency admissions rates fell by 19 per 1, 000 people in the years following the intervention (95% confidence interval [17, 21]) in the intervention city, relative to the comparison population. This effect was greater among more disadvantaged populations, narrowing socioeconomic inequalities in emergency admissions. The findings suggest that similar approaches could be an effective component of strategies to reduce unplanned hospital admissions elsewhere.